The half life of Valery K : a novel - Pulley, Natasha (Bloomsbury Publishing, 2022)
Sent to a mysterious unnamed city in Soviet Russia, former nuclear specialist Valery Kolkhanov must serve out his prison sentence studying the effect of radiation on local animals and struggles to find answers about what is being hidden from the thousands who live in the town.